Blue-green inclusions in neutrophils and monocytes:critical risk findings? - Huerto Aguilar, José Luis (2023)
Objective. To determine whether the presence of blue-green inclusions in neutrophils and monocytes should be considered a critical risk result (CRR). Methods. A review of scientific articles published between 2017 and 2023 was performed to assess whether the presence of blue-green inclusions matches the definition of CRR. Results. The finding of blue-green inclusions has been associated with an elevated risk of short-term mortality and is usually associated with severe liver damage. However, it has also been reported in clinically stable patients. Conclusions. Blue-green inclusions should be assessed based on the patient's clinical condition and in conjunction with other laboratory findings. We cannot state that the isolated presence of these inclusions can be considered a CRR.